Long-Term Safety, Tolerability and Survival in Patients with Pulmonary Arterial Hypertension Treated with Macitentan: Results from the SERAPHIN Open-Label Extension - Souza, Rogério; Delcroix, Marion; Galié, Nazzareno; Jansa, Pavel; Mehta, Sanjay; Pulido, Tomás; Rubin, Lewis; Sastry, B K S; Simonneau, Gérald; Sitbon, Olivier; Torbicki, Adam; Boyanova, Neli; et al. (Advances in therapy, 2022)
INTRODUCTION: In SERAPHIN, a long-term, event-driven, double-blind randomised controlled trial in pulmonary arterial hypertension (PAH), macitentan 10 mg significantly reduced the risk of morbidity/mortality compared with placebo. Its open-label extension study (SERAPHIN OL) further assessed long-term safety and tolerability of macitentan 10 mg in PAH patients. METHODS: Patients in SERAPHIN who completed the double-blind treatment period or experienced a morbidity event during the study could enter SERAPHIN OL. Patients received macitentan 10 mg once daily, and safety and survival were assessed until end of treatment (+ 28 days). Two overlapping sets were analysed for safety: (1) all patients in SERAPHIN OL (OL safety set); (2) patients randomised to macitentan 10 mg in SERAPHIN (long-term safety/survival set). Survival was evaluated as an exploratory endpoint in the latter set. RESULTS: Of 742 patients randomised in SERAPHIN, 550 (74.1%) entered SERAPHIN OL (OL safety set); 242 patients were randomised to macitentan 10 mg in SERAPHIN (long-term safety/survival set). Median (min, max) exposure to macitentan 10 mg was 40.1 (0.1, 130.5) months (2074.7 patient-years; OL safety set) and 54.7 (0.1, 141.3) months (1151.0 patient-years; long-term safety/survival set). Safety in both analysis sets was comparable to the known safety profile of macitentan. Kaplan-Meier survival estimates (95% CI) at 1, 5, 7 and 9 years were 95.0% (91.3, 97.1), 73.3% (66.6, 78.9), 62.6% (54.6, 69.6) and 52.7% (43.6, 61.0), respectively (long-term safety/survival set; median follow-up: 5.9 years). CONCLUSIONS: This analysis provides the longest follow-up for safety and survival published to date for any PAH therapy. The safety profile of macitentan 10 mg over this extensive treatment period was in line with that observed in SERAPHIN. As the majority of patients were receiving other PAH therapy at macitentan initiation, our study provides additional insight into the long-term safety of macitentan, including as part of combination therapy. TRIAL REGISTRATION: ClinicalTrials.gov Identifiers: NCT00660179 and NCT00667823.
Keywords: SERAPHIN; Open-label extension; Safety; pyrimidiny; výsledek terapie; Endothelin receptor antagonist (ERA); Macitentan; familiární plicní arteriální hypertenze; lidé; Combination therapy; Familial Primary Pulmonary Hypertension; Sulfonamides; Long-term outcomes; Treatment Outcome; plicní arteriální hypertenze; sulfonamidy; Pulmonary Arterial Hypertension; Tolerability; Survival; Pulmonary arterial hypertension (PAH); Pyrimidines; Humans